A relação entre o processo cumulativo e a teoria quantitativa da moeda: uma análise da abordagem monetária de Wicksell e de algumas interpretações posteriores - Martins, Darcio Genicolo (2007)
The main goal of this thesis is to analyze Wicksell s monetary approach, with focus on the Cumulative Process. This is made through the reconstruction of theoretical and practical context in which this theory was originated, underlying its relation with the Quantitative Theory of Money. The modern debate on the quantitative character of the Wicksell s view is also analyzed. The thesis is divided in four fundamental parts: (i) the analysis of the institutional and economic environment of XIX century, focusing on the English monetary controversies; (ii) the description of the two positions in Monetary Theory that, according to Wicksell, synthesized the debate: Quantitative Theory of Money Ricardo s version and the Tooke s monetary approach; (iii) the analysis of Wicksell s monetary approach with emphasis of the Cumulative Process analysis; (iv) a brief description of Humphrey, Patinkin, Haavelmo e Leijohnufvud conceptions about the Cumulative Process and their respective opinions about the quantitative characteristic of the Wicksell s model